Nucleolar Dominance in a Tetraploidy Hybrid Lineage Derived From Carassius auratus red var. () × Megalobrama amblycephala () - Cao, Liu; Qin, QinBo; Xiao, Qiong; Yin, HongTing; Wen, Jin; Liu, QiWen; Huang, Xu; Huo, YangYang; Tao, Min; Zhang, Chun; Luo, Kaikun; Liu, ShaoJun (Frontiers in Genetics, 2018)
Nucleolar dominance is related to the expression of 45S rRNA genes inherited from one progenitor due to the silencing of the other progenitor’ s rRNA genes. The knowledge of understanding the nucleolar dominance in polyploidy hybrid animals is scarce. Based on the obtained tetraploidy hybrid lineage including F1 allotetraploids (4n = 148) and F2 autotetraploids (4n = 200) derived from the distant hybridization of Carassius auratus red var. (2n = 100) (♀) × Megalobrama amblycephala (2n = 48) (♂) , in this study, we analyzed the changes regarding the genetic traits and expression of 45S rRNA genes in F1 and F2. Results showed that nucleolar dominance from the female parent was established in F1 and it was inherited in F2, suggesting that tetraploidization can lead to rapid establishment of nucleolar dominance in the hybrid origin’s tetraploid lineage. These results provides new insights into the formation of the nucleolus dominance in polyploidy hybrid animals, which are of significance for the evolution of hybrids in vertebrates.